A Motion Planning Algorithm in a Figure Eight Track - Jardon, Cristian; Sheppard, Brian; Zaveri, Veet (The PUMP Journal of Undergraduate Research, 2023)
We design a motion planning algorithm to coordinate the movements of two robots along a figure eight track, in such a way that no collisions occur. We use a topological approach to robot motion planning that relates instabilities in motion planning algorithms to topological features of configuration spaces. The topological complexity of a configuration space is an invariant that measures the complexity of motion planning algorithms. We show that the topological complexity of our problem is 3 and construct an explicit algorithm with three continuous instructions